Immunometabolic capacities of nutritional fatty acids in regulation of inflammatory bone cell interaction and systemic impact of periodontal infection - Döding, Annika; Zimmermann, Svenja; Maghames, Ahmed; Reimann, Michael; Symmank, Judit; Thürmer, Maria; Gräler, Markus H.; Wolf, Michael; Jacobs, Collin; Koeberle, Andreas; Sigusch, Bernd; Schulze-Späte, Ulrike (Frontiers in Immunology, 2023)
Introduction: Novel preventive strategies in periodontal disease target bacterial-induced inflammatory host response to reduce associated tissue destruction. Strategies focus on modulation of tissue-destroying inflammatory host response, particularly reduction of inflammation and promotion of resolution. Thereby, nutrition turned out to be a potent immunometabolic non-pharmacological intervention. Human studies demonstrated benefit of olive oil-containing Mediterranean-style diets (MDs) with its main component monounsaturated fatty acid (FA) oleic acid (OA (C18:1)). Hence, nutritional OA strengthened the micro-architecture of alveolar trabecular bone and increased circulating pro-resolving lipid mediators following bacterial inoculation with periodontal pathogen Porphyromonas gingivalis, contrary to saturated FA palmitic acid (PA (C16:0)), which is abundant in Westernstyle diets. Additional, generalized distribution of inflammatory pathway mediators can occur in response to bacterial infection and compromises systemic tissue metabolism and bone homeostasis distant from the side of infection. Whether specific FA-enriched nutrition and periodontal inoculation are factors in systemic pathology that can be immune-modulatory targeted through dietary substitution is unknown and of clinical relevance. Methods: Normal-weight C57BL/6-mice received OA-or PA-enriched diets (PA-ED, OA-ED, PA/OA-ED) or normal-standard-diet (n=12/group) for 16 weeks and were orally infected with P.gingivalis/placebo to induce periodontal disease. Using histomorphometry and LC-MS/MS, systemic bone morphology, incorporated immunometabolic FA-species, serological markers of bone metabolism and stress response were determined in addition to bone cell inflammation and interaction in vitro.Results: Opposite to OA-ED, PA-ED reduced systemic bone microarchitecture paralleled by increased lipotoxic PA-containing metabolite accumulation in bone. Substitution with OA reversed bone-destructive impact of PA, which was accompanied by reduced diacylglycerols (DAG) and saturated ceramide levels. Further, PA-associated reduction in mineralization activity and concomitant pro-inflammatory activation of primary osteoblasts were diminished in cultures where PA was replaced with OA, which impacted cellular interaction with osteoclasts. Additionally, PA-ED increased osteoclast numbers in femurs in response to oral P.gingivalis-infection, whereas OA-ED reduced osteoclast occurrence, which was paralleled by serologically increased levels of the stress-reducing lipokine PI(18:1/18:1).OA-substitution reverses bone-destructive and pro-inflammatory effects of PA and eliminates incorporated lipotoxic PA-metabolites. This supports Mediterranean-style OA-based diets as preventive intervention to target accumulation of PA-associated lipotoxic metabolites and thereby supports systemic bone tissue resilience after oral bacterial P.gingivalis-infection.